Detection of oncological diseases in patients with pelvic organ prolapse. Case report - Dmitrii V. Baibuz; Oleg L. Molchanov; Zhanna V. Glushchenko; Yanina A. Lebedeva; Sergei V. Utkin; Artem A. Kravtsov; Rustam A. Shakhaliev; Polina D. Baibuz (IP Berlin A.V., 2021)
Pelvic organ prolapse is a common benign disease among women that is characterized by an isolated or combined descent of the anterior, posterior vaginal wall, uterus, and vaginal dome after hysterectomy. Given the fact that most of the operations are performed among middle-aged and elderly patients, the probability of detecting previously undiagnosed tumor of the abdominal cavity and pelvic region increases, which may be due to the limited volume of basic preoperative diagnosis. The purpose of our report is to draw the attention of clinicians to the problem of insufficient examination of women when planning treatment of pelvic organ prolapse on the example of our experience in managing a patient with this pathology in combination with pelvic tumor.